Medical-surgical management and clinical outcome in cervical abscesses - Andrea Melis; Francesco Riu; Caterina Kihlgren; Antonio Piras; Davide Rizzo; Alessandro Sotgiu; Matthew Donadu; Donatella Usai; Stefania Zanetti; Francesco Bussu (Journal of Infection in Developing Countries)
Introduction: This study aims at defining through a retrospective evaluation, the clinical parameters affecting the clinical course and consequently the management of patients presenting with cervicofacial abscesses.